Financial Decision Making-Skills among Managers of Small and Medium En-terprises in Relation to Business Performance - Racaza, John Philip S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The financial environment of a company is a main factor for the business success, especially SMEs forced to be highly efficient in allocating their limited resources to ensure survival and generate profits by financial constraints. This study aimed to look into the relationship of financial decision skills among managers of SMEs and business performance in Dapitan and Dipolog Cities, Zamboanga del Norte, Philippines during calendar year 2018. The study utilized the quantitative method. A standardized questionnaire checklist was made. The respondents were managers and employees. Secondary data from financial statement was also utilized, and the use of financial ratio was made in determining the business performance of SMEs. The main statistical tools used were frequency count, mean computations, analysis of variance, and Pearson r product moment coefficient of correlation. The study revealed that managers of Small and Medium Enterprises in Dapitan and Dipolog Cities only exhibits intuitive skill to cash ratio and rational skill to debt ratio. These findings support the claim that managers or owners practice intuitive skills and rational skills were effective in dealing their financial obligations. The researcher recommended that managers of SMEs should participate in training and seminars to enhance and develop the exact skills in financial decision-making that are attributable to the business performance.